Social capital in online environments: Effects of Social Structure on Academic Performance in an Online University - Agustí Canals; Josep Cobarsí-Morales; Eva Ortoll (Online Learning)
The idea of social capital as the value obtainable from an individual’s social relationships has been used to study many organizational and social settings, but rarely virtual environments. We use data from an online higher education institution to examine how an individual’s social capital derived from her position in the social structure influences her performance levels. We confirm that social capital has a significant effect on achievement. Firstly, we find that centrality and cohesion in social networks have a positive effect. Secondly, we show how the network structure counts and how diversity in relationships is important. Having access to heterogeneous peers also increases the performance level in learning processes. These findings suggest that the proven importance of social capital in face-to-face situations might be translated into virtual environments and support the need to build or enhance ICT-mediated students' social networks in distance learning.